A CE-FL based method for real-time detection of in-capillary self-assembly of the nanoconjugates of polycysteine ligand and quantum dots. (8th May 2018) - Wang, Jianhao; Zhu, Zhilan; Qiu, Lin; Wang, Jianpeng; Wang, Xiang; Xiao, Qicai; Xia, Jiang; Liu, Li; Liu, Xiaoqian; Feng, Wei; Wang, Jinmei; Miao, Peng; et al.
Abstract: Small molecules with free thiol groups always show high binding affinity to quantum dots (QDs). However, it is still highly challenging to detect the binding capacity between thiol-containing molecules and QDs inside a capillary. To conquer this limitation, a capillary electrophoresis with fluorescence detection (CE-FL) based assay was proposed and established to investigate the binding capacity between QDs and a poly-thiolated peptide (ATTO 590-DDSSGGCCPGCC, ATTO-C4). Interestingly, the results showed that interval time had a great influence on QDs and ATTO-C4 self-assembly, which can be attributed to longer interval time benefitting the binding of QDs to ATTO-C4. The stability assays on ATTO-C4-QD assembly indicated that high concentration of imidazole or GSH had a high capability of competing with the bound ATTO-C4, evidenced by dramatically dropping of S 625 / S 565 ratio from 0.78 to 0.30 or 0.29. Therefore, all these results above suggested that this novel CE-FL based detection assay could be successfully applied to the binding studies between QDs and thiol-containing biomolecules.